The Development of Customer Self-Service Prototype for Readymix Concrete After Sales Service Using Design Thinking Method - Agung Hardiyanto; Erma Suryani (Publikasi Indonesia, 2024)
In the rapidly evolving digital era, companies face challenges in improving customer service. This research focuses on the development of a web-based Customer Self-Service (CSS) prototype for PT. Adhimix RMC Indonesia uses the Design Thinking method. The main goal is to identify customer needs, solve service problems, and create an effective communication system. The method used includes five stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test. Data was collected through surveys, interviews, and prototype testing. The results showed that the prototype developed was able to improve service efficiency and customer satisfaction with key features such as shipment tracking and cast schedules. However, further integration with internal systems and user training is still needed for optimal deployment. In conclusion, web-based CSS development can be an innovative solution in improving after-sales service, strengthening customer relationships, and improving the competitiveness of companies in the construction industry.